Cancer risks from exposure to vehicular air pollution: a household level analysis of intra-ethnic heterogeneity in Miami, Florida. Issue 1 (2nd January 2017) - Chakraborty, Jayajit; Collins, Timothy W.; Grineski, Sara E.
ABSTRACT: Quantitative environmental justice (EJ) research has relied on aggregated data from census units to determine disproportionate hazard exposure. Additionally, variables typically used to analyze ethnic inequities in exposure (e.g., percent Hispanic) are too broad and assume a degree of homogeneity that may not exist, given the diversity of ethnic minority populations. We address these limitations through a study that utilizes primary household level survey data and cancer risk estimates from the National-Scale Air Toxics Assessment (NATA) to analyze intra-ethnic inequities in exposure to vehicular air pollutants in the Miami metropolitan area, Florida. Our analysis disaggregates the Hispanic category based on five characteristics (language proficiency, U.S. citizenship, nativity, unemployment status, and national origin) and finds that risk burdens are significantly higher for Hispanic respondents who are foreign-born, unemployed, and of Cuban origin. Findings highlight the advantages of downscaling EJ analyses to the household level and considering intra-ethnic heterogeneity in EJ research and policy.